2003
DOI: 10.1099/jmm.0.04927-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meningococcal vaccination with combined serogroups A and C polysaccharide vaccine on carriage of Neisseria meningitidis C

Abstract: Two studies of meningococcal carriage state were carried out in Galicia (Spain) before and after a mass vaccination campaign between December 1996 and January 1997 against Neisseria meningitidis serogroup C with meningococcal serogroups A and C polysaccharide vaccine. The studies covered two areas with different incidence rates of meningococcal disease in 1996 (high and low incidence). Carriage rates of serogroup C showed a decrease in both areas, 47 and 65 % respectively, before and after the vaccination. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Although the numbers are small, the level of carriage of serogroup C meningococci (5%; n ϭ 2) was comparable to the equivalent population at the time of the outbreak (7). These results are consistent with observations that immunization with capsular polysaccharide alone may not eliminate carriage of the corresponding meningococcal serogroup (12,6). Carriage of serogroup B meningococci was significantly higher than carriage of serogroup C, with colonization detected in 14% (n ϭ 6) of individuals at some point in the study.…”
Section: Discussionsupporting
confidence: 81%
“…Although the numbers are small, the level of carriage of serogroup C meningococci (5%; n ϭ 2) was comparable to the equivalent population at the time of the outbreak (7). These results are consistent with observations that immunization with capsular polysaccharide alone may not eliminate carriage of the corresponding meningococcal serogroup (12,6). Carriage of serogroup B meningococci was significantly higher than carriage of serogroup C, with colonization detected in 14% (n ϭ 6) of individuals at some point in the study.…”
Section: Discussionsupporting
confidence: 81%
“…All showed a higher overall carriage rate in vaccinees than controls (only two statistically significant); one reported a lower carriage rate of serogroup C meningococci 1 year post‐vaccination in vaccinees (Aceitero 2000). A before‐and‐after study of a mass group A + C polysaccharide vaccination campaign conducted in Spain (Fernandez et al. 2003) found a significant reduction in carriage of serogroup C strains in vaccinated children living in a high‐incidence area but not in children living in a low‐incidence area.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies involved controlled trials (Gotschlich et al 1969;Artenstein et al 1970;Devine et al 1970;Wenzel et al 1973;Makela et al 1975;Wahdan et al 1977;Greenwood et al 1978;Sivonen 1981;Blakebrough et al 1983;Bjune 1992;Boslego et al 1995;Perkins et al 1998), 10 studies evaluated carriage preand post-vaccination (Bosmans et al 1980;Masterton et al 1988;Dimartino et al 1990;Stroffolini et al 1990;Maiden et al 2002;Fernandez et al 2003;Djibo et al 2004;Eslami-Nejad et al 2005;Caugant et al 2006;Mueller et al 2006) and seven were cross-sectional surveys carried out post-vaccination (Hassan-King et al 1988;Neal et al 1998;Smith et al 1999;Aceitero 2000;Cardenosa et al 2001;Dominguez et al 2001;Pavlopoulou et al 2004).…”
Section: Description Of Studies Reviewedmentioning
confidence: 99%
“…The study demonstrated a decrease of carriage rate of serogroup C 1 year after vaccination. The decline in prevalence of N. meningitidis serogroup C was especially considerable in 10-14-and 15-19-year-olds, but not in the 5-9-year-olds (Fernandez et al, 2003). Culturing of nasopharyngeal swabs, 3 weeks after vaccination with the polysaccharide A/C vaccine in the training centre for army medical officers in Italy, revealed that the percentage of isolates belonging to serogroup C was significantly reduced from 6 to 0 .…”
Section: Effect Of Vaccination On Carriagementioning
confidence: 90%